Determine the prevalence of Brucella spp. and Leptospira spp. in blood samples by multiplex polymerase chain reaction collected from cattle, sheep and goats in herds located in provinces of Iran (Veterinary Science Development, 2014)
Leptospirosis and brucellosis are common zoonosis that affect many species of mammals mostly causing economical losses. Further, very important fact is huge danger for human and animal health around the world. The purpose of the study is to determine the prevalence of Brucella spp. and Leptospira spp. using multiplex polymerase chain reaction (mPCR) method, in blood samples collected from cattle, sheep and goats. In this study, a total number of 250 blood samples (5 cc of blood with ethilen diamin tetra asetic acid) were collected randomly from 100 cattle, 80 sheep and 70 goats located on 6 herds in Chaharmahal Va Bakhtiari and Esfahan provinces, Iran. After DNA extraction and setting of mPCR for Brucella spp. and Leptospira spp. mPCR products were screened. The DNA of these microorganisms was detected by multiplex PCR from 31 and 21 out of 100 cattle, respectively. Four of 70 goat’s blood samples from goat breeding farms were positive for Leptospira spp. and 11 were positive for Brucella spp. Out of 80 sheep blood samples 23 were positive for Brucella spp. and 14 for Leptospira spp. The results of the present study show ruminant as an important reservoir for transmission of these zoonotic diseases to humans in Iran. mPCR has the ability to concurrently detect both Brucella and Leptospira species from blood samples of ruminants. The convenience and the possibility of detection of both bacteria at a time, strongly support the use of this mPCR for routine diagnostics.